The Effect of Rosa Damasecana Aromatherapy on the Level of Anxiety During the First Active Phase of Labor - Sinaga, Elvina Sari; Harahap, Rahmaini Fitri; Saragih, Ruth Sarah Julfrida; Kaban, Fitriyana Br (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
Anxiety can weaken uterine contractions or reduce maternal pushing power (power), thereby inhibiting labor progress and potentially leading to prolonged labor. Many pregnant women experience anxiety during childbirth. Aromatherapy can help relax the body, improve mood, and refresh the mind. Rose essential oil has been shown to reduce relative sympathetic nerve activity by 40% and decrease plasma adrenaline concentrations. This study used a quasi-experimental design with a one-group pretest-posttest with control group. The population and sample included all mothers who gave birth at the Lena Barus Binjai Clinic between October and December 2024, totaling 20 individuals, divided into intervention and control groups. The result of the t-test showed a p-value of 0.000 (<0.05), indicating a significant effect of Rosa damascena aromatherapy on reducing anxiety levels during the first stage of active labor. The mean ranks for the control and intervention groups were 5.70 and 15.30, respectively, with sum ranks of 57.00 and 153.00.